Optimal use of peritoneal dialysis fluids in type 2 diabetes mellitus patients - Ryckelynck, Jean-Philippe; Allard, Catherine; Cousin, Maud; Hurault de Ligny, Bruno; El Haggan, Wael; Lobbedez, Thierry (Néphrologie & thérapeutique, 2006)
The glucose side-effects, the main osmotic agent in conventional peritoneal dialysis (PD) solutions, are structural and functional changes of the peritoneal membrane, especially diabetic alterations in the microvasculature. Therefore, hyperpermeability with high small solutes transport and less ultrafiltration necessitates more and more high glucose concentration solutions. Glucose degradation products (PDF) and advanced glycation end-products (AGE) are formed and may induce peritoneal membrane alterations. More biocompatible solutions have to be used with less PDF and physiological pH. Icodextrin containing PD solutions have beneficial effect on sustained ultrafiltration for long dwells in PD, limitating fluid overload common in PD patients above all during peritonitis episodes. Amino acid-based PD solutions contribute to the prevention of malnutrition often observed in the diabetic PD population.